2009
DOI: 10.1111/j.1749-4486.2009.01932.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial to compare postoperative pain in children undergoing tonsillectomy using cold steel dissection with bipolar haemostasis versus coblation technique

Abstract: The findings do not confirm the hypothesis that tonsillectomy undertaken in children, with the coblator device, is associated with lower levels of postoperative pain, but do indicate that less analgesia is required by the coblator patients in the first 12 h postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 16 publications
1
42
0
Order By: Relevance
“…On comparing the pain scores in the immediate postoperative evening after 06 hours of surgery there was no statistically difference in the pain scores between the two groups as shown in Table 1. These findings were in consonance with other authors such as Shah, Magdy & Parker D. 5,7,13 In our study there was no statistical difference in the pain score on the first postoperative day between the 2 groups however on the 7 th postoperative day the pain score was more for the coblation arm and it was statistically significant as in Table 1. In our study we found that the postoperative pain is equal on both sides in the early period whereas in the later postoperative period, cold steel provides better pain relief than coblation technique.…”
Section: Discussionsupporting
confidence: 93%
“…On comparing the pain scores in the immediate postoperative evening after 06 hours of surgery there was no statistically difference in the pain scores between the two groups as shown in Table 1. These findings were in consonance with other authors such as Shah, Magdy & Parker D. 5,7,13 In our study there was no statistical difference in the pain score on the first postoperative day between the 2 groups however on the 7 th postoperative day the pain score was more for the coblation arm and it was statistically significant as in Table 1. In our study we found that the postoperative pain is equal on both sides in the early period whereas in the later postoperative period, cold steel provides better pain relief than coblation technique.…”
Section: Discussionsupporting
confidence: 93%
“…12 Shapiro and Bhattacharryya (2007) compared the intraoperative efficiency and postoperative recovery between dissection and coblation tonsillectomy (age 2-16) over 14 postoperative days, including the day of operation, found that there was no statistically significant difference in the mean pain scores between two procedures and this result is similar to the result of our study. 15 In another study done by Parker et al (2009), with respect to postoperative pain and return to normal diet, he discovered that coblation did not offer the significant advantage over dissection method. 9 In addition, another study done by Businco & Tirelli (2011), showed that the day of pain-free was 4.8 vs. 9.4 for dissection, also coblation group stopped liquid diet sooner (day 5 vs. day 9) and lost fewer school days than dissection children.…”
Section: Resultsmentioning
confidence: 99%
“…15 In another study done by Parker et al (2009), with respect to postoperative pain and return to normal diet, he discovered that coblation did not offer the significant advantage over dissection method. 9 In addition, another study done by Businco & Tirelli (2011), showed that the day of pain-free was 4.8 vs. 9.4 for dissection, also coblation group stopped liquid diet sooner (day 5 vs. day 9) and lost fewer school days than dissection children. 3 Roje et al (2009) did a comparison study between the two techniques; he revealed that children operated on by coblation technique faster resumed normal physical activities in 2 vs. 4 days and the result was statistically significant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peritonsillar infiltration of different types of drugs in children undergoing adenotonsillectomy has been cited many times during the past years, using local anesthetics [4], opioids [5,6], corticosteroids [7][8][9], ketamine [10,11], gabapentine [12] and even non-pharmacologic interventions [13] as adjuvant local analgesic compounds.…”
Section: Introductionmentioning
confidence: 99%